Potential of Jackfruit Waste for Biogas, Briquettes and as a Carbondioxide Sink-A Review - Nsubuga, Denis; Banadda, Noble; Kabenge, Isa; Wydra, Kerstin D. (Journal of Sustainable Developmen, 2020)
One of the key aspects of a green economic development model of a country is to develop indigenous resources and local expertise while utilizing sustainable technologies. This review explored the possibilities of utilizing jackfruit waste for production of biogas, briquettes and biochar. In many of the developing countries, there is huge potential for organic waste conversion into appropriate energy solutions. These can contribute to developing rural areas especially small holder farmers and diversifying the available energy sources. Biomass waste like jackfruit waste when managed well can produce bio-energy, but also the GHG emissions need to be reduced from unmanaged, decomposing organic material. When put to use, agricultural biowastes like jackfruit waste could be used as raw materials in the production of bio-products (biofuels, biochar, bio pesticides), briquettes, among others. The biochar can be mixed with the soil producing carbon-rich soils and contribute to CO2 sequestration and soil fertility. This paper reviews works focused on using jackfruit waste for anaerobically producing of biogas, briquettes and biochar for improved crop production. The paper concluded that jackfruit waste can anaerobically decompose to produce biogas and it can also be used for briquette production. It was further concluded that jackfruit waste can undergo decomposition at high temperatures to produce biochar which can be incorporated into the soil creating a CO2 sink hence helping in mitigating the effects of the climate change.
Keywords: Anaerobic digestion; Biochar, biogas; Briquettes; Co-digestion; Jackfruit and terra preta